Działalność Towarzystwa Polska Sztuka Stosowana (1901–1913) – próby nawiązania współpracy między producentami, projektantami i odbiorcami - Wójcik, Agata (Załącznik Kulturoznawczy, 2019)
Active between 1901–1903, the Polish Applied Art Society (the TPSS), sought to achieve three essential aims: ‘to spread admiration for Polish applied art, to facilitate its development and to introduce it to the industry’. This article presents the activities of the TPSS, whose aim was to establish cooperation with manufacturers and workshops as well as to acquire commissions from institutions and private individuals. Under this cooperation, the TPSS opened competitions, provided designs or employed artists as artistic directors. The Society succeeded in establishing cooperation with a number of printing and publishing houses; it also finalised an agreement with Antonina Sikorska’s kilim workshop, Czernichów. What is more, by employing TPSS members as artistic directors, it exerted influence on ceramics manufacturing in J. Niedźwiecki & Co. Faience Factory in Dębniki and on that of stained glass in Stanisław Gabriel Żeleński’s Stained Glass and Mosaic Works in Krakow. The TPSS was also commissioned to design interiors and furniture by private individuals and by institutions. However, no cooperation was established with any furniture factory. Contrary to its plans, the Society did not succeed in directly influencing furniture manufacturing; its activities had the features of exclusive artistic craft. This is also how they were received by the audience. Summing up and closing its activities, the Society set a goal for Polish applied art, which would be to create two types of businesses – ones which would manufacture things ‘of quality, in design, material, and workmanship’ and others for ‘machine manufacturing’ and producing cheap objects without, however, ‘lowering standards of taste and workmanship’.